2012
DOI: 10.2164/jandrol.111.013599
|View full text |Cite
|
Sign up to set email alerts
|

Orthogonal Polarization Spectral Imaging: A Novel Tool for Examination of Microcirculatory Changes in the Testis

Abstract: Testicular torsion is a surgical emergency in urologic practice. Many models have demonstrated the relationship between the degree and duration of the torsion and the subsequent damages of the testis, but there are as yet no suitable methods for visualization of the testicular microcirculation in this condition. We aimed to use orthogonal polarization spectral (OPS) imaging to observe the microcirculatory changes in the testis after ischemia-reperfusion (I/R) challenge, and to compare this technique with that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…This situation causes compression in the testicular microcirculatory system (venous-arteriolar) and alteration of the vascular diameter. 26,27 Studies have shown that testicular venous congestion causes formation of vascular microthrombi that induce the intrinsic coagulation pathway. 27,28 Furthermore, hypoxia has been shown to increase the formation of microthrombi and production of endothelin-1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This situation causes compression in the testicular microcirculatory system (venous-arteriolar) and alteration of the vascular diameter. 26,27 Studies have shown that testicular venous congestion causes formation of vascular microthrombi that induce the intrinsic coagulation pathway. 27,28 Furthermore, hypoxia has been shown to increase the formation of microthrombi and production of endothelin-1.…”
Section: Discussionmentioning
confidence: 99%
“…30 These published findings suggest that the MPV is elevated in testicular torsion because this condition causes vascular pathology. [26][27][28] Erythrocyte sedimentation rate and C-reactive protein, which are acute-phase markers, have been shown to be elevated during the clinical examination leading to a diagnosis of testicular torsion. 3,31 The MPV was shown to be significantly higher in patients with acute pancreatitis compared with control subjects, 32 but a significantly lower MPV was detected in paediatric patients with acute appendicitis.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported to increase in urological vascular pathologies such as ischaemic priapism (Ufuk et al, ). Studies have shown that testicular venous congestion causes formation of vascular microthrombi that induce the intrinsic coagulation pathway, and MPV might be elevated in TT because this condition causes vascular pathology (Bajory, Szabo, Deak, Varga, & Pajor, ; Cicek et al, ; Rattansingh, Adamson, & Cosgrove, ). We suspected that after spermatic cord torsion, platelet activity may be increased and more neonatal platelets are generated due to the formation of microthrombi in testicular parenchyma.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, it is a powerful approach to investigate alterations of the reproductive organs under pathological conditions as well as the development of new therapies. In line with this interpretation is, for example, the assessment of testicular alterations (Nagler et al, 1987;Bajory et al, 2011;Turner, 2011) regulation of blood pressure in pregnancy (Burke et al, 2010) and the investigation of prostate cancer development/progression and new therapies (Frost et al, 2005;Abedinpour et al, 2011).…”
Section: Reproductive Systemmentioning
confidence: 91%